PENGARUH BUDAYA ORGANISASI, KOMUNIKASI ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. PLN (Persero) AREA SEMARANG - Herlista, Adinda; Waloejo, Handoyo Djoko; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed  to determine the effect of variable organizational culture, organizational communication and motivation on employees performance at PT. PLN (Persero) Semarang area. The population of this study were all employees of PT. PLN (Persero) Semarang area  96 people total by spreading using census or sampling method saturated. Measurement scale using Likert scale. In the analysis of the data using simple linear regression and multiple regression test with SPSS 16.0. From the analysis of the data is known that organizational culture variables affect employee performance at 31.3 percent. Organizational communication variables affect the performance of employees at 23.5 percent. Motivational variables affect the performance of employees at 45.2 percent. Taken together organizational culture, organizational communication and motivation affects the performance of employees at 52.6 percent. This means better or higher organizational culture, organizational communication, and motivation of employees it is expected that the better performance and higher as well.Based on these research  result, the management of PT. PLN (Persero) Semarang area needs to consider the conditions of the organizational culture that have been implemented of the company. Organizational communication level also should be maintained properly so that employees can be more effective at work. Companies also need  to increase the motivation of its employees. So employees can be more motivated in their works to improve its performance. With the increasing of the performance the company's goals of the PT. PLN (Persero) Semarang area can be reached.